Molecular Epidemic Characteristics and Genetic Evolution of Porcine Circovirus Type 2 in Henan, China - Zhifeng Peng; Huifang Lv; Han Zhang; Li Zhao; Huawei Li; Yanyu He; Kangdi Zhao; Hongxing Qiao; Yuzhen Song; Chuanzhou Bian (Veterinary Sciences)
The widespread distribution and genetic diversity of porcine circovirus type 2 (PCV2) seriously threatens the swine industry worldwide. This study investigates the molecular epidemiology of PCV2 in Henan Province (2020–2023) through PCR screening (385 samples) and whole-genome sequencing (34 strains). The overall detection rate was 71.17% (274/385), with annual rates of 81.16% (112/138) in 2020, 72.41% (84/116) in 2021, 62.50% (55/88) in 2022, and 53.49% (23/43) in 2023, indicating a declining trend. Phylogenetic analysis revealed the dominance of the PCV2d genotype, comprising 82.4% (28/34) of sequenced strains. Evolutionary analysis identified strong negative selection pressure on ORF2, with an elevated substitution rate of 1.098 × 10−3 ssy. These findings provide critical insights into the predominance and adaptive evolution of PCV2d, and significantly improve our understanding of its genetic diversity and evolutionary dynamics.